Application of model free active disturbance rejection controller in nuclear reactor power control. (October 2021) - Sun, Aodi; Songmao, Pu; He, Zhengxi; Xiao, Kai; Sun, Peiwei; Wang, Pengfei; Wei, Xinyu
Abstract: The power control of nuclear reactors is the key to the safe operation of nuclear reactors. At present, PID controllers are still used in most industrial control. Although PID has the advantages of simple design and easy parameter tuning, it is still difficult to overcome its own shortcomings in the control of complex systems and large-scale parameter adjustment. Model-Free active disturbance rejection control(MF-ADRC) and PID are control method that do not require model information. This study compares the control performance of PID and MF-ADRC in nuclear power control. First, three different core models are established, and the power MF-ADRC and PID controller of LBFR is designed. The performance of MF-ADRC and PID is compared through reactive disturbance and wide-range power adjustment. Finally, the performance of MF-ADRC and PID control is compared through the control of different core power. The results show that MF-ADRC has the same parameters to be tuned as PID; PID is difficult to balance overshoot and settling time, but MF-ADRC does a good job in this aspect; PID and MF-ADRC have good robustness, In terms of results, MF-ADRC is more satisfactory.